2020
DOI: 10.3389/fphar.2019.01630
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity as a New Tool to Evaluate the Response to Omalizumab and Mepolizumab in Severe Asthmatic Patients: A Pilot Study

Abstract: Asthma is a chronic inflammatory airway disease, representing one of the most severe pathologies in developed countries. Based on a report of the World Health Organization (WHO), it affects about 300 million people worldwide. Few studies have analyzed the effects of daily life physical activity (PA) levels in patients with asthma: moreover, little research has been carried out on PA levels in patients suffering from severe asthma (SA). This study aimed to investigate the PA levels in two groups of patients suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…To our knowledge, the present is the second study to investigate the effect of any asthma therapy on DPA. Carpagnano et al [ 39 ] found significant improvements in daily step count and energy expenditure in 30 patients treated with biological therapy (omalizumab or mepolizumab) for six months compared to patients on traditional therapy. The magnitude of improvement with biologic therapy was notably larger than in our study, as the patients almost doubled their daily steps (from 3806 ± 421 to 6545 ± 844) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present is the second study to investigate the effect of any asthma therapy on DPA. Carpagnano et al [ 39 ] found significant improvements in daily step count and energy expenditure in 30 patients treated with biological therapy (omalizumab or mepolizumab) for six months compared to patients on traditional therapy. The magnitude of improvement with biologic therapy was notably larger than in our study, as the patients almost doubled their daily steps (from 3806 ± 421 to 6545 ± 844) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of pharmacological therapies such as biologics on physical activity levels in asthma, however, is largely unknown. To our knowledge, Carpagnano and colleagues were the first to explore the effect of biologics on physical activity levels in severe asthma compared to traditional therapies ( 98 ). In this pilot study, published in 2020, fifty patients with severe asthma who were treated with either high-dose ICS with a LABA/LAMA and a biologic [omalizumab ( n = 15) or mepolizumab ( n = 15)], or traditional therapy (ICS/LABA/LAMA/OCS, n = 20) were followed over 6 months ( 98 ).…”
Section: Managing Asthma With Extrapulmonary Comorbidities/traitsmentioning
confidence: 99%
“…To our knowledge, Carpagnano and colleagues were the first to explore the effect of biologics on physical activity levels in severe asthma compared to traditional therapies ( 98 ). In this pilot study, published in 2020, fifty patients with severe asthma who were treated with either high-dose ICS with a LABA/LAMA and a biologic [omalizumab ( n = 15) or mepolizumab ( n = 15)], or traditional therapy (ICS/LABA/LAMA/OCS, n = 20) were followed over 6 months ( 98 ). While improvements in physical activity levels [average steps per day (SPD) and total daily energy expenditure (Total EE)] were observed both groups (biologic therapy and traditional therapy), a significantly greater increase in physical activity was reported in patients who received a biologic add-on therapy ( 98 ).…”
Section: Managing Asthma With Extrapulmonary Comorbidities/traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…A correct nutrition, adequate physical activity and abstention from smoking are important measures against aging and prevention of cardiovascular disease and cancer (Larsen et al, 2019). Data literature reported that physical activity reduces or slows the onset of diseases related to obesity, inducing a considerable weight loss and having beneficial and anti-inflammatory effects, reducing the production of free radicals, and favouring greater resistance to stress and prolonging lifespan (Carpagnano et al, 2020). Furthermore, a healthy lifestyle induces the expression of a many genes involved in the repair of cellular damage and reduces the expression of genes involved in the mechanisms of oxidative stress and inflammation (Nigro 2016).…”
Section: Introductionmentioning
confidence: 99%